Aktualisasi Kecerdasan Interpersonal Kepala Sekolah dalam Pengembangan Mutu Pendidikan - Novan Ardy Wiyani; Ismi Nurprastika; Ahmad Sahnan (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2020)
The role of the leader in an organization has a very important role. Leaders who have interpersonal intelligence have compassion, a sense of responsibility, cooperate, have a social spirit, can communicate and interact with others. A leader is a person who has unique abilities and advantages so that he can influence others to jointly carry out certain activities for the achievement of a goal. The ability of the principal to build relationships will lead to the development of quality education. This study aims to determine the actualization of the dimensions of social sensitivity, the actualization of the dimensions of social insight, and the actualization of social communication dimensions in developing the quality of education. This research is descriptive qualitative research with a phenomenological approach. Data were collected using interviews, observation, and documentation. The data were then analyzed using three stages, namely data reduction, data presentation, and drawing conclusions. This study indicates that: first, there is actualization or real manifestation of the dimensions of social sensitivity in the form of empathy, social sensitivity, and the ability to observe changes in school elements. Second, the actualization of the dimensions of social insight in the form of the ability to handle the problems at hand. Third, the social communication dimension's actualization in the form of the ability to establish communication with school members to achieve educational goals. These forms of actualization become a way to develop a quality education. Keywords: Interpersonal Intelligence, Principal, Quality Development, Education